Enhancing Revisit Intentions: The Role of Perceived Value, Brand Experience, and Tourist Satisfaction in Bukit Lawang Ecotourism - Sinaga, Aprizal Haris; Rini, Endang Sulistya; Harahap, Hamdani (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of perceived value and brand experience on revisit intention through tourist satisfaction as an intervening variable at the Bukit Lawang ecotourism destination. This research employs an associative quantitative approach. The study population comprises tourists who have visited Bukit Lawang, with a sample of 180 respondents selected using purposive sampling. Primary data were collected through questionnaires, while secondary data were obtained through documentation studies. Data analysis utilized the Structural Equation Modeling (SEM) method with SmartPLS version 3.0 as the analytical tool. The results show that perceived value has a positive and significant effect on tourist satisfaction and revisit intention. However, brand experience does not influence tourist satisfaction but has a positive and significant effect on revisit intention. Tourist satisfaction mediates the effect of perceived value and brand experience on revisit intention. This research provides practical implications for tourism managers to improve service quality and create unique experiences to enhance tourists' intention to revisit.